2016
DOI: 10.1111/nph.14343
|View full text |Cite
|
Sign up to set email alerts
|

Dominant mycorrhizal association of trees alters carbon and nutrient cycling by selecting for microbial groups with distinct enzyme function

Abstract: While it is well established that plants associating with arbuscular mycorrhizal (AM) and ectomycorrhizal (ECM) fungi cycle carbon (C) and nutrients in distinct ways, we have a limited understanding of whether varying abundance of ECM and AM plants in a stand can provide integrative proxies for key biogeochemical processes. We explored linkages between the relative abundance of AM and ECM trees and microbial functioning in three hardwood forests in southern Indiana, USA. Across each site's 'mycorrhizal gradien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
137
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 186 publications
(160 citation statements)
references
References 67 publications
(98 reference statements)
10
137
3
Order By: Relevance
“…Alternatively, differences in microbial growth and turnover may reflect differences in the microbial community composition (Kallenbach et al., ). In agreement with previous studies on the active soil microbial community (Cheeke et al., ), we observed differences in the GluN:GalN ratio indicating differences in the microbial community composition across a gradient of ECM dominance.…”
Section: Discussionsupporting
confidence: 93%
“…Alternatively, differences in microbial growth and turnover may reflect differences in the microbial community composition (Kallenbach et al., ). In agreement with previous studies on the active soil microbial community (Cheeke et al., ), we observed differences in the GluN:GalN ratio indicating differences in the microbial community composition across a gradient of ECM dominance.…”
Section: Discussionsupporting
confidence: 93%
“…While changes in bacterial community may be influenced by overall fungal community composition, these shifts in bacterial community composition are tightly coupled to %AM colonization (a metric of belowground C allocation) suggesting that plant responses to N fertilization feedback on bacterial community structure and function (Figure c). While we cannot rule out that N‐induced declines in total fungal biomass led to reductions in liginolytic enzyme activity (DeForest et al., ; Frey et al., ; Treseder, ; Wallenstein et al., ), the dominance of AM trees in our plots, whose inorganic nutrient economy is largely driven by bacteria, suggests that free‐living fungi may not be an important driver of N deposition responses in AM‐dominated systems (Cheeke et al., ; Phillips, Brzostek, & Midgley, ).…”
Section: Discussionmentioning
confidence: 84%
“…Here we did not focus on P resorption because Rosling et al () have investigated P cycling at these same field sites and found little effect of mycorrhizal type on litter P and inorganic P cycling, suggesting that differences in P resorption between ECM and AM forests should be relatively small in our temperate forests. The three forest sites – Griffy Woods (GW; 39°11′ N, 86°30′ W), Morgan Monroe State Forest (MMSF; 39°19′ N, 86°25′ W) and Lilly‐Dickey Woods (LDW; 39°14′ N, 86°13′ W) – differ in species composition, soil type and land‐use history (Cheeke et al, ), yet all are within 30 km from one another and thus experience the same climate. At each site, 15 permanent research plots (15 m × 15 m) were established that vary in the relative abundance of ECM and AM trees, offering a unique opportunity to explore relationships between mycorrhizal dominance and resorption.…”
Section: Methodsmentioning
confidence: 99%